Explaining Children’s News Avoidance During the COVID-19 Pandemic - Ebbinkhuijsen, Ming; Buijzen, Moniek; de Leeuw, Rebecca; Kleemans, Mariska (Frontiers in Psychology, 2022)
Despite growing concerns that children (8–13 years old) tend to avoid the news, the reasons why have received little research attention. Therefore, the current study aims to develop and test a model conceptualizing the relations between children’s news consumption, news avoidance, emotional responses (negative emotions and anxiety-related behaviors), and parent and child mitigation strategies. The model was tested using data collected during the first year of the COVID-19 pandemic. The current, preregistered, survey study was part of a longitudinal project and used data from the second wave. Data were collected in November/December 2020 among 510 children (Mage = 10.40; 53.72% girls). Findings showed that children who consumed more news during the pandemic avoided pandemic news less often. Children who experienced more anxiety-related behaviors regarding pandemic news avoided pandemic news more often. The relation between news consumption and emotional responses was stronger for children who experienced restrictive parental mediation more often, indicating that this was not an effective parental mediation strategy for tempering their emotional responses. Children with higher levels of emotional responses used reactive coping strategies more often. However, this did not seem to be an effective strategy against pandemic news avoidance because none of the strategies had a negative relation with pandemic news avoidance. Distancing was even positively related to pandemic news avoidance. Although the current study was not able to fully unravel how news avoidance-related constructs relate to one another, we were able to get some important insights guiding future research. Specifically, it is of crucial importance to unravel the mechanisms that increase the chance of children’s news avoidance and those that mitigate it, to build interventions to counteract news avoidance and to protect children from the negative emotional consequences by news consumption.